Connect Program: Providing International Teaching Assistants a Firsthand Look at Undergraduate Life. (7th October 2020) - Hatcher, Molly; Amayreh, Wafa; Struve, Laura
Abstract: This chapter describes a program aimed to help international graduate students navigate linguistic, pedagogical, and cultural challenges they face as new college instructors by connecting them with undergraduates who share personal insights and campus resources.